Process-based modeling of root water uptake and plant available water at the field scale - Melo, Marina Luciana Abrêu de (2024)
Water transfer processes in the soil-plant-atmosphere continuum can be described by physical principles integrated into modeling frameworks. This thesis aims to enhance the assessment of crop water requirements in agricultural systems by i) evaluating a process-based root water uptake (RWU) model for the simulation of crop growth and water use at the field scale and ii) proposing a novel process-based method to determine plant available water (PAW). Chapter 1 consists of a general introduction to the research. Chapter 2 was dedicated to reviewing the assumptions of soil water balance and RWU models that do not explicitly consider the effect of soil hydraulic properties on crop evapotranspiration. The arguments were illustrated by comparative analyses that evidenced the superiority of process-based models for the simulation of soil water dynamics and water use by different crops. Chapters 3 and 4 are parts of a study aimed at evaluating a process-based modeling framework (the SWAP agro-hydrological model with the RWU function MFlux) to simulate crop transpiration, drought stress, crop growth, soil water dynamics, and soil water balance components for scenarios of soybean and wheat cultivation in a winter-dry climate in southeast Brazil. In Chapter 3, a sensitivity analysis to RWU parameters of the SWAP/MFlux model performed with different methods revealed that the root length density is the most sensitive parameter for drought stress predictions. In Chapter 4, SWAP/MFlux was calibrated and evaluated using data from field experiments of soybean and wheat crops in Piracicaba, São Paulo state, Brazil. Crop parameters were calibrated using observed crop growth variables, such as leaf area index, crop height, and above-ground dry mass. The soil hydraulic parameters and some RWU parameters were optimized by inverse modeling using observed data of soil water content and crop evapotranspiration. After the optimization procedure, there was a good agreement between measured and simulated variables at a daily time step. The chapter also includes long-term simulations of crop yield, water productivity, irrigation amounts, and soil water balance for three water management scenarios, showing that an irrigation criterion based on relative crop evapotranspiration may reduce the irrigation amount and increase the water productivity of irrigation with a slight decrease in crop yield compared to a criterion based on total available water. Chapter 5 introduces a novel process-based approach to determining PAW (the flux-based method, FBM). The proposed FBM explicitly considers soil hydraulic properties, rooting characteristics, and atmospheric water demand. After applying the FBM to several scenarios, its robustness was evidenced, representing an important contribution to vadose zone research. Chapter 6 concludes this thesis with a general discussion and future outlooks.